Presupuestos participativos (PPs) e instituciones participativas (IPs) en Brasil: criterios (y marco) para la evaluación de experiencias y casos - Pires, Valdemir Aparecido [UNESP]; Nebot, Carmen Pineda (My University, 2011)
This paper identifies relevant criteria for evaluation of participatory budgeting and participatory institutions that are currently adopted by governments of both Brazil and elsewhere, highlighting the importance of a comprehensive assessment that integrates all these criteria. Finally, it is recommended to pay special attention to assessing the desirability of these institutions, which are not always positively for theories on democracy

En este artículo se identifican diversos criterios relevantes para la evaluación de los presupuestos participativos y las instituciones participativas que son adoptados actualmente por gobiernos tanto de Brasil como de otros lugares del mundo, destacando la importancia de una evaluación global que integre todos estos criterios. Finalmente, se recomienda prestar especial atención a la evaluación de la deseabilidad de esas instituciones, que no siempre son percibidas positivamente por las teorías sobre la democracia.

O número do volume foi incluído (valor arbitrário) apenas para aceite do sistema, pois a revista não o adota.
Participatory budgets (PBs) and participatory institutions (PIs) in Brasil: criteria (and framework) for the evaluation of experiences and cases
Keywords: Participatory democracy; participatory institutions; participatory budgeting; evaluation of public policies; Democracia participativa; Instituciones participativas; Presupuesto participativo; Evaluación de políticas públicas.